AMBIT NORM OF PROOF IN CASES OF MURDER OF A NEWBORN BABY BY HIS MOTHER - Лихова, Софія Яківна; Рибікова, Ганна Володимирівна; Грекова, Лілія Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: the article deals with the study of application the norms of proof law in the criminal trials relatively art. 117 of the Criminal Code of Ukraine in order to ensure the uniformity in judicial practice. The proofs from the verdicts of courts of the first instance are analyzed. Methods of research: the dialectical method of cognition, general scientific and special methods were used. Results: has been developed the science-based approach to form the permissible norm of proof in cases of murder of a newborn baby by his mother. Discussion: search for ways to advance law enforcement practice.